Potential of Traditional Markets in Improving The Economy of Muslim Traders (Case Study in Pasar Rabu, Galing District, Sambas Regency) - Sri Deti (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
ABSTRACT This study seeks to analyze and qualitatively descriptive of the potential of the Wednesday Market in Galing District, Sambas Regency, and how the market can improve the economy of Muslim traders. Data collection techniques in the form of observation, interviews, and documentation. While the primary data source is Muslim traders and the secondary data source is the Head of Galing Village. The data validity techniques used are triangulation techniques and continuous observation techniques. The results of the study revealed that the traditional market which is a type of weekly market in the Galing District has the potential to improve the economy of traders, especially Muslim traders because Pasar Rabu has met the analysis criteria in determining market potential, namely meeting the needs and desires of the community, having clear market segmentation, meet targets, added value, product life span and fair market competition. Supporting and inhibiting factors for traders in improving the economy at Pasar Rabu, namely: Supporting Factors: Adequate human resources and well-managed natural resources, the ability to use technology and capital resources, and the level of security that is maintained. Inhibiting factors: lack of government attention, unavailability of infrastructure needed by traders, and global inflation.